Transformative outcomes: assessing and reorienting experimentation with transformative innovation policy. (31st July 2021) - Ghosh, Bipashyee; Kivimaa, Paula; Ramirez, Matias; Schot, Johan; Torrens, Jonas
Abstract: The impending climate emergency, the Paris agreement and Sustainable Development Goals demand significant transformations in economies and societies. Science funders, innovation agencies, and scholars have explored new rationales and processes for policymaking, such as transformative innovation policy (TIP). Here, we address the question of how to orient the efforts of science, technology, and innovation policy actors to enable transformations. We build on sustainability transitions research and a 4-year co-creation journey of the TIP Consortium to present twelve transformative outcomes that can guide public policy agencies in evaluating and reformulating their projects, programmes, and policies. We illustrate the transformative outcomes in two empirical cases: transitions towards mobility-as-a-service in the Finnish transport system and the emergence of speciality coffee in Colombia. We argue that the twelve transformative outcomes can guide public policy agents to fundamentally transform their ways of thinking and operation in advancing transformative change.